GENETIC DIVERSITY AND CHARACTERIZATION OF COMMON BACTERIAL BLIGHT RESISTANCE IN COMMON BEAN (Phaseolus vulgaris L.) IN NORTHERN NIGERIA USING GENOME-WIDE ASSOCIATION STUDIES (FUDMA JOURNAL OF SCIENCES, 2025)
This research aimed to identify and characterize genes associated with Common Bacterial Blight (CBB) resistance in Nigerian common beans using Genome-Wide Association Studies (GWAS). A total of 200 common bean accessions, along with their phenotypic data, were used for the study. The accessions were genotyped using the BARCBean6K_3 Infinium BeadChips, and SNPs were called using GenomeStudio V2011.1. A filtering process was applied to remove SNPs with a high missing data rate (>10%), a high heterozygosity rate (>10%), or a low minor allele frequency (
Keywords: Phaseolus vulgaris; Bacterial blight resistance; GWAS; SNP markers; FarmCPU; Disease-responsive genes